Toward the development of an instrument to evaluate learner-generated comics - Azman, Farah Nadia; Zaibon, Syamsul Bahrin; Shiratuddin, Norshuhada (Faculty of Computing, Universiti Teknologi Malaysia, 2016)
A considerable amount studies in the area of user-generated content (UGC) have highlighted the advancement of learner-generated content. Essentially, learner-generated comics (LGC) production refers to a technology-enhanced educational approach of empowering learners to creatively innovate digital comics.This paper describes a work in progress development of questionnaires for assessing LGC production model. In line with the learner-generated content quality indicator, LGC evaluation must have emphasis on both process and the produced content itself. Therefore, two major instruments are designed to validate the LGC production model and measure the quality of a LGC product.By adapting relevant comics, creative product, conceptual model constructs, attributes and dimensions from questionnaires by prior scholars, future work will focus on validating the constructed instruments.